Politeness strategies in twitter updates of female English language studies Malaysian undergraduates - Marlyna Maros,; Liyana Rosli, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Twitter is now developing as a rich research site for scholars who studied online interaction, information dissemination and other plethora of subjects. Taking on this new development, this paper aims to contribute to the field of politeness and English language studies in computer-mediated communication (CMC) by showcasing the politeness strategies in Twitter updates and by predicting how the tweets could potentially misfire. A total of 776 tweet updates produced by 9 female undergraduates, active users of Twitter within two months, were documented and open-ended questionnaire responses were collected for in-depth findings. The data were analysed using Brown and Levinson’s (1987) Politeness Strategies. The findings show that the participants employed four politeness strategies with positive politeness employed the most, followed by bald-on record, off-record with the least employed being negative politeness. Positive politeness is believed to be used the most because of the nature of CMC which promotes interpersonal communication and expression among its users. Although the participants employed all four politeness strategies, it is important to be aware that misunderstanding could still easily occur due to the absence of other communication cues in virtual ‘faceless’ communication. Hence, this study showed that the overuse of profanity, ambiguous indirect strategy and failure to comply with the 140-character limits in Twitter are some of the reasons that might cause misfire to happen.